Systems‐of‐systems modeling using a comprehensive viewpoint‐based SysML profile. Issue 3 (19th April 2017) - Mori, Marco; Ceccarelli, Andrea; Lollini, Paolo; Frömel, Bernhard; Brancati, Francesco; Bondavalli, Andrea
Abstract: In recent years, more and more efforts have been devoted in supporting the design of systems‐of‐systems (SoS). Designing such systems is a multidisciplinary problem which involves considering emergent phenomena, assuring the achievement of dependability/security requirements, guaranteeing system responsiveness, and supporting dynamicity/evolution and multicriticality of provided services. A first step towards a viable design approach is to provide a conceptual model of SoS which captures SoS concepts, and their interrelationships aiming at enhancing the understandability of SoS to stakeholders and providing the basis for further automated analysis. In this context, the AMADEOS European project is bringing together researchers and practitioners to provide the support to design SoS starting from the definition of a domain specific ontology serving as a vocabulary for SoS. Our contribution consists in the modeling of the key SoS concepts and relationships defined in AMADEOS adopting a systems modeling language visual modeling language. We propose a systems modeling language profile for SoS, and we show its applicability in a Smart Grid scenario. We show how to use the profile in a model‐driven engineering process to support different types of analyses, and we discuss how to integrate the profile in a user‐friendly model‐driven engineering tool for SoS rapid modeling, validation, code‐generation, and simulation.